Pioglitazone: A review of analytical methods - N. Satheeshkumar; S. Shantikumar; R. Srinivas (Elsevier, 2014)
Pioglitazone is an oral anti-hyperglycemic agent. It is used for the treatment of diabetes mellitus type 2. It selectively stimulates nuclear receptor peroxisome proliferator-activated receptor gamma (PPAR-gamma). It was the tenth-best-selling drug in the U.S. in 2008. This article examines published analytical methods reported so far in the literature for the determination of pioglitazone in biological samples and pharmaceutical formulations. They include various techniques like electrochemical methods, spectrophotometry, capillary electrophoresis, high-performance liquid chromatography, liquid chromatographyâelectrospray ionization-tandem mass spectrometry and high-performance thin layer chromatography. Keywords: Pioglitazone, Analytical methods, Diabetes mellitus type 2